2022
DOI: 10.3390/ijerph19020851
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress at Work and Associated Factors among E-Waste Workers in French-Speaking West Africa

Abstract: Perceived stress at work is an important risk factor that affects the mental and physical health of workers. This study aims to determine the prevalence and factors associated with perceived stress in the informal electronic and electrical equipment waste processing sector in French-speaking West Africa. From 14 to 21 November 2019, a cross-sectional survey was carried out among e-waste workers in five countries in the French-speaking West African region, and participants were selected by stratified random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The majority of the studies (14 out of 17) used a cross-sectional design, and the remaining three studies [ 21 , 35 , 36 ] used a cohort study design. Thirteen of the included studies were conducted among male e-waste workers, and only three studies [ 30 , 32 , 37 ] included female participants. Of the 17 studies, eight did not include a reference population, and the sample size ranged between 45 [ 38 ] and 740 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies (14 out of 17) used a cross-sectional design, and the remaining three studies [ 21 , 35 , 36 ] used a cohort study design. Thirteen of the included studies were conducted among male e-waste workers, and only three studies [ 30 , 32 , 37 ] included female participants. Of the 17 studies, eight did not include a reference population, and the sample size ranged between 45 [ 38 ] and 740 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the included studies were conducted among male e-waste workers, and only three studies [ 30 , 32 , 37 ] included female participants. Of the 17 studies, eight did not include a reference population, and the sample size ranged between 45 [ 38 ] and 740 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it was not statistically significant, the trend increased positively for ERI with income. A study by Kêdoté and colleagues found a relationship between increased perceived stress and insufficient income among e-waste workers [ 11 ]. However, this study was conducted among informal e-waste workers in West Africa where the workers struggled to meet personal basic and familial needs such as nutrition, housing, and health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have looked at psychosocial factors of work among waste workers found the prevalence of perceived stress among e-waste and solid waste workers to be high due to the nature of their work (e.g., ergonomic challenges, exposure to chemicals, limited personal protective equipment use). However, these studies were focused on West Africa and Southeast Asia [ 10 , 11 , 12 ]. To our knowledge, there have been no studies focused on psychosocial factors among United States solid waste workers, or among US waste workers overall.…”
Section: Introductionmentioning
confidence: 99%